The Impact of Corruption on the Efficiency of Customs Clearance in the Arab Countries - Mohammed, Mahmoud Magdy Barbary (The Arab Journal of Administration, 2024)
Customs is one of the most important economic authorities in all countries because of its roles on several levels. On the one hand, customs are considered a line of state defense against smuggling and the illegal entry of products that are not allowed to be traded. On the other hand, customs represent an element of protection for locally made products from the competition of foreign products, and on the third hand Customs represents a source of government revenue, and with these important roles at the practical and political level, customs are not devoid of roles specific to economic policy, whether fiscal or commercial, and therefore the customs system must be dealt with cautiously as a result of the interference of the concerned authorities in dealing with it, in addition to that, customs transactions affect the movement of Trade and as a result of human intervention in these transactions, the customs clearance process may become subject to being affected by intentional and unintended practices of administrative and financial corruption, which may negatively affect all the aforementioned goals, and the Arab countries, as developing countries, suffer from some problems related to the variables under study, whether the nature of the management of the system Customs duties or the presence of corruption within some government systems, which adds more importance to the research.